The Economics of Mass Shootings - Abel Brodeur; Hasin Yousaf (Institute of Labor Economics (IZA), 2019)
We perform an empirical investigation of the socioeconomic determinants and consequences of all mass shootings in the U.S. from 2000 to 2015. We first manually search for and collect information on perpetrators. We find that approximately 40% (45%) of shooters were in financial distress (unemployed or out of the labor force) at the moment of the shooting, suggesting that economic distress may trigger rise in shooting. We then investigate the economic consequences of mass shootings. In order to obtain the causal effects of shootings, we exploit the inherent randomness in the success or failure of mass shootings. We find that, on average, successful mass shooting have economically significant negative effects on targeted counties' employment and earnings. As well, successful mass shootings decrease housing prices and consumer confidence and increase absenteeism. Last, we employ an instrumental variable strategy and show that national media coverage of mass shootings exacerbate their local economic consequences.
Keywords: D74; C13; P16; 330; mass shootings; employment; consumer confidence; absenteeism; media coverage